1996
DOI: 10.1046/j.1525-1438.1996.06030241.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glutathione S-transferase pi and cisplatin resistance in human ovarian cancer

Abstract: Glutathione S‐transferase π (GSTπ) expression in tumor cells is thought to relate to cisplatin resistance. We attempted to clarify immunohistochemically the correlation between GSTπ expression and clinical response in ovarian cancer. Fifty‐nine patients with ovarian cancer underwent initial debulking surgery and received from three to five courses of cisplatin‐based chemotherapy after surgery. Immunostaining for GSTπ was performed on formalin fixed sections of the patients’ tumor by the streptoavidin‐biotin‐pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The products, in the form of mercapturates, are subsequently eliminated from the cell . As GSH and the GST superfamily play an important role in the mechanism of anticancer drug resistance, , including metal-based drugs, efforts have focused on the development of GST inhibitors and GST-activated prodrugs as means of sensitizing drug-resistant cancer cells to treatment. In this context, ethacrynic acid ([2,3-dichloro-4-(2-methylene-1-oxobutyl)­phenoxyl]­acetic acid, EA-H; Figure ) is a versatile, water-soluble compound that modulates GST activity. EA-H conjugation to GSH may occur in a spontaneous fashion or via the catalytic action of the major classes of GST (α, μ, and π), with the π isozyme being the most active .…”
Section: Introductionmentioning
confidence: 99%
“…The products, in the form of mercapturates, are subsequently eliminated from the cell . As GSH and the GST superfamily play an important role in the mechanism of anticancer drug resistance, , including metal-based drugs, efforts have focused on the development of GST inhibitors and GST-activated prodrugs as means of sensitizing drug-resistant cancer cells to treatment. In this context, ethacrynic acid ([2,3-dichloro-4-(2-methylene-1-oxobutyl)­phenoxyl]­acetic acid, EA-H; Figure ) is a versatile, water-soluble compound that modulates GST activity. EA-H conjugation to GSH may occur in a spontaneous fashion or via the catalytic action of the major classes of GST (α, μ, and π), with the π isozyme being the most active .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In the past, we reported that the overexpression of GSTπ is strongly related to resistance to cisplatin and to prognosis in patients with ovarian cancer on immunohistochemical study. 7 Some patients with ovarian cancer cannot undergo an operation because of their poor condition and must receive neoadjuvant chemotherapy. In such cases, it is useful to check the overexpression of GSTπ before therapy when the patient is suspected of having ovarian cancer by ascites cytology and images.…”
mentioning
confidence: 99%